A13 Comprehensive Health Impact Assessment for Active Travel: A "PASTA" project approach. Issue 2 (June 2015) - Rojas-Rueda, David; Anaya, Esther; Avila-Palencia, Ione; Brand, Christian; Cole-Hunter, Thomas; de Nazelle, Audrey; Dons, Evi; Frick, Fabienne; Gerike, Regine; Götschi, Thomas; Kahlmeier, Sonja; Mueller, Natalie; et al.
Abstract: Background: Health impact assessment (HIA) is a combination of methods by which a policy or intervention may be assessed and judged for its potential effects on the health of the population. The HIA is classified in four levels of depth: desk-based, rapid, intermediate and comprehensive. These different levels vary in resources, capacity, duration and level of health impacts. Comprehensive HIA is the more complex, collecting and analyzing data from different sources. It also offers more accurate estimates of the health impacts related with multiple pathways and health determinants. PASTA (Physical Activity through Sustainable Transport Approaches) is a European project with detailed case studies in seven cities (Antwerp, Barcelona, London, Orebro, Rome, Vienna and Zurich) that focuses on promoting and assessing active travel and developing a new comprehensive health impact assessment (HIA) model for active transport. Methods: Identifying stakeholders and experts in each city. conduct workshops (one in each city) with stakeholders and experts. Perform individual interviews (12 in each city) with experts and stakeholders. Conduct a systematic review on active travel HIA, risk assessments and cost benefits analysis published in peer review journals. Conduct systematic reviews to identify the most robust epidemiological evidence between health exposures and outcomes. Build a HIA model quantifying the health risk and benefits related with active travel interventions and measure the uncertainties. Report and communicate the results to stakeholders, experts and citizens. Results: The workshops and interviews showed their importance to identify 1) main interventions or policies on active travel in the local context; 2) the requirements, priorities and expectations of HIA in the decision making process; 3) local and regional data sources; and 4) key stakeholder networks for participation and dissemination. The systematic review of HIA showed that there is further improvement needed in 1) the identification and quantification of health determinants (e.g. physical activity, traffic hazards, air pollution, noise, etc.); 2) selection of robust dose-response functions based on the weight of evidence; 3) the harmonization of methods, definitions and assumptions used; and 4) the close collaboration between urban planners, transport practitioners and health experts. Conclusions: The novel approach of integrating stakeholder and expert workshops, interviews, systematic reviews and evidence based approaches in the HIA process is a necessary advancement for comprehensive HIA for active travel.